2021
DOI: 10.1177/21501327211024391
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Use Is Not Associated with COVID-19 Diagnosis

Abstract: This analysis tested the hypothesis that current e-cigarette use was associated with an increased risk of SARS-CoV-2 infection in patients seeking medical care. E-cigarette and conventional cigarette use were ascertained using a novel electronic health record tool, and COVID-19 diagnosis was ascertained by a validated institutional registry. Logistic regression models were fit to assess whether current e-cigarette use was associated with an increased risk of COVID-19 diagnosis. A total of 69,264 patients who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 20 publications
2
23
1
Order By: Relevance
“…Whereas previous studies have shown no association with greater risk for being infected with COVID-19 for those individuals who vape (use e-cigarettes). 14 This analysis of clinical data collected from COVID-19 positive patients revealed a higher frequency of COVID-19 symptoms among those individuals who vape when compared to those who do not vape. Using logistic regression, we identified a significantly higher frequency of Covid-19 symptoms such as headaches, myalgia, anosmia/dysgeusia, chills, lightheadedness, chest pain, nausea/vomiting, and diarrhea among those individuals who used only e-cigarettes; whereas those who vaped and smoked had a significantly higher occurrence of dyspnea and ED visits (related and not related to COVID-19).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Whereas previous studies have shown no association with greater risk for being infected with COVID-19 for those individuals who vape (use e-cigarettes). 14 This analysis of clinical data collected from COVID-19 positive patients revealed a higher frequency of COVID-19 symptoms among those individuals who vape when compared to those who do not vape. Using logistic regression, we identified a significantly higher frequency of Covid-19 symptoms such as headaches, myalgia, anosmia/dysgeusia, chills, lightheadedness, chest pain, nausea/vomiting, and diarrhea among those individuals who used only e-cigarettes; whereas those who vaped and smoked had a significantly higher occurrence of dyspnea and ED visits (related and not related to COVID-19).…”
Section: Discussionmentioning
confidence: 83%
“… 9 - 12 An article published by Gaiha et al 13 in July 2020, concluded that COVID-19 was “five times more likely among ever users of c-cigarettes and 7 times more likely amongst dual users.” However, another study found that using e-cigarettes did not pose an increased risk for COVID-19. 14 There have been several letters and publications 15 , 16 which have been critical of the quality of data and analysis used by Gaiha et al 13 Aside from the content and potential harms of e-cigarettes, sharing of vaping devices has been raised as a potential concern for the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Generally, individuals who live in rural regions, have lower income or education, and racial and ethnic minorities are less willing to receive the vaccine. [9][10][11][12][13] Consistent evidence from numerous countries finds that smokers are less likely than non-smokers to be infected by COVID-19, [14][15][16][17] but if infected, smokers have had higher disease severity. 18,19 Typically, more severe cases result in higher usage of healthcare resources, including longer hospital stays, which makes it important to understand vaccination perceptions and hesitancy among tobacco users to help avert overloading the healthcare system.…”
Section: Introductionmentioning
confidence: 98%
“…Levels of cotinine, the metabolite of nicotine, are comparable in smokers and vapers. 10 ECIG vaping has variably been associated with increased risk, 11 and no increased risk, 12 for COVID-19 diagnosis.…”
Section: Introductionmentioning
confidence: 99%